2006
DOI: 10.1159/000092242
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Repeated Oral Administrations of the Oral Adsorbent AST-120 on Serum Creatinine and Other Markers of Renal Function

Abstract: Background: AST-120 is an orally administered adsorbent used in Japan for prolonging time to initiation of hemodialysis and improving uremic symptoms in patients with chronic kidney disease (CKD). As AST-120 is suspected to reduce the progression of CKD by adsorbing renal toxins in the gastrointestinal tract, the objective of the current study was to determine whether binding of AST-120 to creatinine in the intestines could acutely alter creatinine balance, thereby limiting the utility of serum creatinine (sCr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 19 publications
(13 reference statements)
0
26
0
Order By: Relevance
“…level, whichever occurred first. Because an earlier study of AST-120 found no significant differences between AST-120-treated and placebotreated patients in 24-hour urinary creatinine excretion and sCr, 31 indicating that inconsequential or no amounts of creatinine were adsorbed by AST-120 in the gut, sCr was determined to be a valid measure of renal function in patients treated with AST-120, and an increase in sCr was selected as a component of the composite end point. The secondary end point was a quadruple composite of the primary end point and death.…”
Section: Assessments and Outcomesmentioning
confidence: 99%
“…level, whichever occurred first. Because an earlier study of AST-120 found no significant differences between AST-120-treated and placebotreated patients in 24-hour urinary creatinine excretion and sCr, 31 indicating that inconsequential or no amounts of creatinine were adsorbed by AST-120 in the gut, sCr was determined to be a valid measure of renal function in patients treated with AST-120, and an increase in sCr was selected as a component of the composite end point. The secondary end point was a quadruple composite of the primary end point and death.…”
Section: Assessments and Outcomesmentioning
confidence: 99%
“…AST-120 takes the form of spherical particles, 0.2-0.4 mm in diameter, composed predominantly of porous carbon material with a high surface area, exceeding over 1600 m 2 /g [Marier et al 2006]. The abundant porosity and its wide distribution provide an extensive and efficient binding surface, which enables selective adsorption and removal of low molecular weight substances from the intestinal lumen.…”
Section: Introductionmentioning
confidence: 99%
“…One concern is that changes in serum creatinine associated with the use of AST‐120 are due to adsorption of creatinine from the gut as opposed to an impact on renal function. However, a recent study evaluated whether the adsorption of creatinine with AST‐120 in the gut would acutely alter creatinine balance, which would limit the meaningfulness of serum creatinine as a measure of disease progression 32 . The study used a two‐way crossover design and found no significant differences in serum creatinine or 24‐h urine creatinine with AST‐120 (9 g/day) versus placebo, thereby indicating that serum creatinine is a valid measure of changes in renal function.…”
Section: Discussionmentioning
confidence: 99%